Clinical presentation and outcome of snakebite cases in a teaching hospital (Bangladesh Medical Journal Khulna, 2021)
Background: Snake bite is an important but under recognised public health issue in Bangladesh. It is one of the important cause of mortality in our country specially in this southern part of Bangladesh.Objective: This study was carried out to evaluate the common type of snake bite in local area with their clinical presentation and outcome of admitted patients in hospital.Methods: Patients of snake bite diagnosed by history and clinical examination were consecutively selected for the study after fulfillment of inclusion criteria in the inpatient department of medicine ward, Khulna Medical College Hospital from July 2017 to June 2018. Data were collected and analysed afterwards.Results: Among 54 snake bite patients 27 (50%) were female and 27 (50%) were male. Twenty nine (53.7%) were venomous snake bite and 25 (46.3%) were non venomous. The common victims were farmers 14 (25.9%) and housewife 19 (36.2%). The bites were commonly encountered during walking (30%) in rural area. Bite also occured during sleeping (20%). The majority of the snake bite was observed during the month of June & July. Total 95% patient applied multiple tight tourniquet in the affected limb. A common local practice was to receive prehospital treatment from 'Ohzas'. Among 29 poisonous cases, drooping of the upper eyelid was present in 29 (100%) patients, External Opthalmoplegia and broken neck sign were present in 19 (66.6%) patients. Among the venomous snake bite cases 25 (93%) patients recovered completely after getting antivenom.Conclusion: Neurological manifestation (Ptosis, Opthalmoplegia, Broken neck sign) are very common in venomous snake bite. Early detection and application of antivenom is needed for better outcome. Treatment of venomous snake bite with Polyvalent serum is successful and safe.Bang Med J Khulna 2020: 53 : 23-26